IMPLEMENTASI PERLINDUNGAN HUKUM TERHADAP HAK CIPTA ATAS BUKU - Risky Amelia; Ahmadi Ahmadi; Eneng Juandini (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Books are a form of creative work that has value. As an object of Intellectual Property Rights, books can have legal protection so that they are not carelessly used, reproduced, and plagiarized by others. Protection of books as creations has been regulated in the provisions of copyright law in Indonesia, namely the Copyright Law, which grants exclusive rights to creators or copyright holders. These rights are inherent to the owner of the rights, so that any use of copyrighted works must be carried out with the permission or approval of the owner of the rights. If a copyright infringement is committed by someone by using, duplicating, publishing, distributing, and taking economic benefits from a book without the permission of the owner of the rights. This not only harms the creator and owner of the rights in terms of economic value but also ignores respect for the results of thought, creativity, and intellectual work. Legal protection for books is important to ensure legal certainty and provide a sense of security for creators and encourage the development of science, education, and culture. This study aims to provide an understanding of the position of books as objects of copyright protection, describe the forms of violations that may occur, and also emphasize the importance of permission in the use of other people's creative works. This research was conducted normatively by examining the provisions of relevant laws and regulations. Research into the legal protection of books as creative works is crucial to understanding the forms of protection provided by laws and regulations, the characteristics of actions that can be considered copyright infringement, and the legal remedies available to creators or copyright holders in the event of a violation. With clear and firm legal protection, it is hoped that books will be recognized as more than just physical objects, but also intellectual works that must be respected and protected from copyright infringement. This understanding can help to sustainably suppress the practice of book piracy in Indonesian society.Keyword : Legal Protections,Copy Rights, Books.